2004
DOI: 10.1007/s00467-004-1584-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of methylprednisolone pulse therapy in steroid-resistant nephrotic syndrome

Abstract: Steroid-resistant nephrotic syndrome (SRNS) in children is intractable, and the optimal treatment regimen is not known. We investigated the efficacy of methylprednisolone pulse therapy (MPT) in SRNS patients. Using only MPT plus heparin, we have treated ten pediatric SRNS patients that were resistant to cyclophosphamide (CPM) or cyclosporin A (CsA) and predicted to have a very poor prognosis. Administration of 30 mg/kg per day methylprednisolone with heparin for 3 days was taken as one course, and this was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…This has been shown to increase the response rate by between 44% [12] and 82% [13], based on protocols derived from the studies of Tune and Mendoza and colleagues [6,14]. In our series we have achieved one of the highest remission rates (73.3%), although, in most cases, the administration of an alkylating agent was required to consolidate remission, administration that has normally taken place in all the studies published, with the exception of the Mori series [15]. As in other studies [16], the MCD patients responded better than the FSGS patients, but not at a level of statistical significance, probably because of the number of cases.…”
Section: Discussionmentioning
confidence: 57%
“…This has been shown to increase the response rate by between 44% [12] and 82% [13], based on protocols derived from the studies of Tune and Mendoza and colleagues [6,14]. In our series we have achieved one of the highest remission rates (73.3%), although, in most cases, the administration of an alkylating agent was required to consolidate remission, administration that has normally taken place in all the studies published, with the exception of the Mori series [15]. As in other studies [16], the MCD patients responded better than the FSGS patients, but not at a level of statistical significance, probably because of the number of cases.…”
Section: Discussionmentioning
confidence: 57%
“…Several retrospective studies have reported that a combination of MPT with cyclosporine and prednisolone produces better outcomes than those previously obtained in patients with FSGS, with remission rates ranging from 84 to 90% [20][21][22]. Other studies have shown that MPT alone is an effective treatment in children with SRNS [17,18]. These results suggest that MPT combined with cyclosporine and prednisolone may improve the remission rate in children with FSGS.…”
Section: Discussionmentioning
confidence: 59%
“…Niaudet et al and others have reported that cyclosporine combined with alternate-day or low-dose steroids produces a higher response rate than cyclosporine monotherapy [5,10,14,15]. Several studies have reported a favorable response to methylprednisolone pulse therapy (MPT) in patients with focal segmental glomerulosclerosis (FSGS) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…In our study, two of 12 children did not require CyA, although they required MPP to obtain remission. In most countries, patients with persistent nephrotic proteinuria after a course of high-dose oral prednisone are considered to be steroid-resistant and are mostly treated with oral CyA [11,12]. However, these treatment protocols are often based on a 6-week prednisone course at disease onset and/or a maximum daily dosage of 80 mg. One may hypothesize SDNS Steroid-dependent nephrotic syndrome; MPP methylprednisolone pulses a Relapses before and after cyclosporine A (CyA) are given as the total number among patients who had been started on CyA during disease course that some of the patients who were considered to be highdegree steroid-dependent in our study would probably be considered as steroid-resistant in several other countries.…”
Section: Discussionmentioning
confidence: 99%